The effect of obsolescence, cost and patent benefit to patent application - Hernandez, Laura F.
The study is a survey on the effect of obsolescence, cost and patent benefit to patent application. It aimed to find out whether the three factors have significant effect on patent application. A survey-questionnaire was designed and used to collect data. The questionnaire consisted of three parts; Part I contained items on demographic characteristics of the respondent; Part II contained the questions that measured the effect of obsolescence, cost and patent benefit to patent application; Part III measured the attitude of the respondent toward patent application given obsolescence, cost and patent benefit. A total of fifty questionnaires were distributed to the designers of selected garment retail stores. The statistical tool used to test for correlation was Pearson's Coefficient of Correlation. R-squared statistics was used to test for the strength of the association among the variables while F statistics was used to test the hypothesis, patent application = obsolescence = cost = patent benefit = 0, or each variable doesn't in any way affect the other. The findings of the study were as follows: 1. There is a significant relationship between the independent and dependent variables of the study. Obsolescence, cost and patent benefit are related to non-patent application. 2. There is an association among the variables but the association is not strong. 3. The hypothesis was rejected at α 0.05 confidence level. Thus, there is at least one variable which has an effect over the other.